Inverse modeling of the ocean and atmosphere - Bennett, Andrew F., 1945- (Cambridge University Press, 2002)
This is a graduate-level book for students of oceanography and meteorology, and anyone interested in combining computer models and observations of the hydrosphere or solid earth. Variational tools and statistical concepts are concisely introduced, applications to contemporary research models are examined in detail and further advanced research topics are discussed.